Manganese-based immunotherapy synergized with novel supramolecular hydrogel: Advancing localized immune activation strategies in squamous cell carcinoma - Tianqing Wang; Xiaopei Hu; Xin Tian; Ying Wang; Shiyu Zhang; Silu Sun; Ning Ji; Xiaobo Luo; Qianming Chen; Xin Zeng; Hang Zhao; Jing Li (Materials & Design)
Head and neck squamous cell carcinoma (HNSCC) presents significant challenges for its treatment, especially for the treatment aimed at preserving maxillofacial function due to its complex anatomical structure, resistance to radiotherapy and chemotherapy, and low intertumoral immunogenicity. In this study, we introduce a novel approach employing manganese-based immunotherapy (Mn-IT) for the effective treatment of HNSCC. Firstly, we used a tumor-immune cell co-culture system to demonstrate that Mn2+ enhances immune cytotoxicity in HNSCC via cGAS-STING activation. Subsequently, we used an orthotopic transplant tumor model to validate that Mn-IT exerts antitumor effects and immune activation in HNSCC. Subsequently, to enhance efficacy and reduce the immune-related side effects of Mn-IT, we utilized the biocompatibility and immunomodulatory potential of inosine to develop a supramolecular hydrogel, guanosine-phenylboronic-tannic acid-phenylboronic-inosine (G-TA-I), through a green and straightforward method. The G-TA-I hydrogel is characterized by its dynamic borate ester-based structure, facilitating localized, sustained release of therapeutics. This hydrogel not only exhibited acceptable biocompatibility and biodegradability but also was able to load and sustain the release of Mn2+ and PD-1 antibody in situ. Finally, we adopted a range of mouse tumor models to reveal that G-TA-I supramolecular hydrogel drug delivery system loaded with Mn2+ and PD-1 antibody could efficiently activate local immunity, effectively combating the occurrence and progression of HNSCC. These findings indicate that the Mn-αPD-1-loaded in situ sustained-release G-TA-I hydrogel represents a novel, safe, and effective cancer therapeutic drug delivery system that can maximize the efficacy of immunotherapy and reduce the side effects of immunotherapy. This supramolecular hydrogel drug delivery system provides a basis for new therapeutic strategies for tumor types such as head and neck tumors that require maximal preservation of the structure and function of the diseased site.